2019
DOI: 10.1155/2019/3438743
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Surface Cracks of Concrete due to Corrosion and Bond Strength (between Steel Bar and Concrete)

Abstract: The current experimental study presents the results of bond strength loss (steel bar concrete) due to the corrosion damage of steel bar specimens, semiembedded in concrete, at various times of exposure to corrosive environment. In this case, a correlation was made between the width of the surface cracks of concrete caused by reinforcing steel corrosion and bond strength for different distances between stirrups and different cover thickness of concrete. The study indicates close relationship between the width o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Correlation between ultimate bond strength ratio and surface crack width. Comparison between recommendations from Model Code 2010[62], results from previous authors[48,58,51,59,52,53] (data derived from plots where not explicitly presented in published work) and results from present study It is reasonable to assume that a local relationship exists between equivalent bond stresses and the total crack width along the bar. The average bond stress ratios can therefore be compared with the mean total crack widths, as shown in the plots ofFig.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Correlation between ultimate bond strength ratio and surface crack width. Comparison between recommendations from Model Code 2010[62], results from previous authors[48,58,51,59,52,53] (data derived from plots where not explicitly presented in published work) and results from present study It is reasonable to assume that a local relationship exists between equivalent bond stresses and the total crack width along the bar. The average bond stress ratios can therefore be compared with the mean total crack widths, as shown in the plots ofFig.…”
mentioning
confidence: 56%
“…Reviews of the relevant literature can be found elsewhere [17,23]. [38,48,7,41,42,43,51,44,3,52,53]; (b) Bond deterioration and corrosion [5,47,39,54,48,49,55,18,50,51,56,16,52,53].…”
Section: Corrosion Products Steel Bar Concretementioning
confidence: 99%
“…On this basis, many researchers have studied the effect of corrosion on bond between steel and concrete [24][25][26][27][28][29][30]. As Maslehuddin et al [27] reported, bond strength of RC specimens without transverse reinforcement increases slightly in low corrosion degree; however, sharp bond loss takes place with the propagation of corrosion.…”
Section: Corrosion Effect On Bond Strengthmentioning
confidence: 99%
“…Testing RC specimens without stirrups, Maslehuddin et al [27] indicated that although a slight improvement of bond strength is demonstrated in low corrosion levels, sharp degradation pf bond strength is recorded as corrosion increases. Recently, experimental studies by Zandi et al [28], Lin et al [29] and Apostolopoulos and Koulouris [30] investigated both the significant role of stirrups spacing and corrosion carrying out eccentric pull out tests on RC elements with usual design values of concrete cover.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of steel bars in concrete reduces the diameter, strength, and elasticity modulus of steel bars, cracks, or even exfoliates concrete cover. It weakens the bond between steel bars and concrete [1][2][3].…”
Section: Introductionmentioning
confidence: 99%